Penerapan IMC (Integrated Marketing Communications) oleh Pemerintahan Kabupaten Sukoharjo pada Kegiatan Sukoharjo Expo 2023 - Nurbani Aisyah, Siti; Rahmat Wisudawanto; Hasbullah Azis (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The success of an event has an impact on improving the image of an institution. A good image of an institution affects public trust and can benefit the institution. One of the events held by the Sukoharjo Government Regency in creating its institutional image is the Sukoharjo Expo. The Sukoharjo Expo is an activity that carries the theme “Ekonomi Kerakyatan, Penggerak Kejayaan Ekonomi Nasional”. The event is an exhibition to commemorate the 77th anniversary of Sukoharjo Regency and support economic recovery for micro, medium, and various fields. The implementation of IMC supports public relations in communicating with the public, especially in promoting activities. This can support institutions to convey strong, clear, and consistent messages so that communicants can truly receive and understand the message. The study aims to categorize and explain the implementation of the IMC strategy in the 2023 Sukoharjo Expo activities. This study used the theory of Morissan (2015) with 7 categories of integrated marketing communications. This research is a qualitative study with data from interviews, observations, and documentation. The sampling technique used purposive sampling. Data analysis used interactive model analysis. The results of the study show that the Sukoharjo Government Regency at the Sukoharjo Expo 2023 event has implemented all 7 theories of Morissan (2015), namely advertising, personal selling, sales promotion, public relations, direct marketing, interactive / internet marketing, and internet marketing. Furthermore, the findings were analyzed using SWOT analysis to determine the strengths, weaknesses, opportunities, and threats.